Phenotype and genotype of hypophosphatasia cases in Saudi Arabia: multi-center case cohort - Alsagheir, Afaf; Mcrabi, Ali; Alquayt, Meshari; Alhuthil, Raghad; Alawi, Afnan; Faqeih, Eissa; Alabdullatif, Abrar Turki; Homyani, Doua Al; AlJohany, Amal; AlOtaibi, Mariam; Rabea, Magdy; AlSayed, Hassan; et al. (Frontiers in Genetics, 2026)
IntroductionHypophosphatasia (HPP) is a rare inherited metabolic disease caused by mutations in the ALPL gene. The disease is heterogeneous, complicating its diagnosis and delaying optimal management, leading to severe or lethal outcomes such as failure to thrive, fragility fractures, bone deformities, delayed motor development, respiratory failure, seizures, and premature death. However, no epidemiological studies on the incidence of HPP in Saudi Arabia have been identified until now. Therefore, the study aimed to describe the phenotype and genotype of Saudi patients with HPP.MethodsThis retrospective multicenter case series included six centers in Saudi Arabia. Paediatrics and adult patients with clinically and genetically confirmed HPP were included between January 2014 and May 2024. Demographic and clinical information, including medical history, clinical, biochemical, genetic, and management data, was collected retrospectively from medical records and summarized descriptively. Additionally, whole-exome sequencing or ALPL next-generation sequencing (NGS) was performed. Furthermore, pre- and post-analysis for patients who received asfotase alfa was performed using the Wilcoxon signed-rank test.ResultsThe study included 19 HPP cases, of whom 68.4% were male. There were five patients with perinatal onset (26.3%), 13 with infantile onset (68.4%), and one with childhood onset (5.3%) of HPP. About 78.9% of patients indicated a family history of HPP; consanguinity was observed in nearly all parents of cases. Bone deformities were observed in all patients, including skull (78.5%), limb (100%), spinal (49.9%), and dental abnormalities (57.9%). Complications such as craniosynostosis (78.5%), nephrocalcinosis (26.3%), kyphoscoliosis (49.9%), and convulsions (26.3%) were also documented, with 4 (21.05%) deaths. Thirteen (68.4%) of our patients received asfotase alfa. All cases tested positive for ALPL variants, with the most common being c.293C>T (p.Ser98Phe) and c.977G>T (p.Gly326Val), both of which were novel and not previously reported.ConclusionOur study highlights HPP’s diverse phenotypes and genotypes in Saudi Arabia, revealing distinct ALPL mutations. We identified a high prevalence of consanguinity and family histories of HPP. Treatment with asfotase alfa was generally effective and safe.